Tillering Potential and Stability of Winter Wheat Varieties Commonly Grown in Kansas - L. O. Pradella; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2023)
The tillering potential and stability of winter wheat (Triticum aestivumL.) can be positive traits by conferring adaptation to distinct production environments. The literature demonstrates a high correlation between the tillering potential and many yield components. However, the actual impact of tillering potential on grain yield is not clear. Our goal was to quantify the tillering potential and stability of a range of winter wheat varieties. Field experiments were conducted in six locations in the state of Kansas during the 2021–2022 season. A complete factorial treatment structure of twenty-five winter wheat varieties by two seeding rates (400,000 seeds per acre and 1.2 million seeds per acre) was established in a randomized complete block design with three or four blocks. We measured the stand count (twenty days after sowing) and the number of stems at the growth stage Feekes 6 in 3 1⁄4 row-feet in each plot. Tillers per plant were modeled as a function of plants per square feet by replication within the environment using non-linear models. Overall, fall precipitation and temperature accumulation partially regulated tiller production, but the major determinant of tillers per plant was the number of plants per area. Different seeding rates led to large differences in population and tiller components, which in compensation only resulted in modest grain yield changes. With few exceptions, varieties tended to be stable in their ranking as a function of the environment; thus, varieties with high tillering potential can be an option to reduce seed costs.
Keywords: winter wheat; varieties; tillering; population; canopy cover